Organic in the Bedroom: The Fertile Vision of Wendell Berry and Humanae Vitae - Parler, Branson L. (Christian scholar's review, 2017)
Most Protestant Christians do not give much attention to the theological and moral dimensions of contraception. In his essay, Branson Parler argues that Wendell Berry’s general critique of the modern mythos helps us to hear Roman Catholic teaching on contraception as resistance to one specific practice entailed by that mythos. Insofar as Protestants recognize that there are theological problems with the modern mythos, then they ought also to reconsider their ethical stance (or lack thereof) on contraception.